Autorzy:Janowicz Jerzy
Wydawnictwo:Nowa Era
Rok wydania:2015
Oblicz 4.4 gwiazdek na podstawie 5 opinii

`a)\ sqrt(3^2+4^2)=sqrt(9+16)=sqrt25=5` 


`b)\ root(3)(3^3+4^3+5^3)=root(3)(27+64+125)=root(3)216=6` 


`c)\ sqrt(1-2+3-4+5-6+7)=sqrt(-1+(-1)+(-1)+7)=sqrt4=2` 


`d)\ sqrt(1+2+3+4+5+6+7+8)=sqrt36=6` 


`e)\ sqrt(2+sqrt(2+sqrt(2+sqrt(2+sqrt(2+sqrt(2+sqrt4))))))=sqrt(2+sqrt(2+sqrt(2+sqrt(2+sqrt(2+sqrt(2+2))))))=` 

`\ \ \ =sqrt(2+sqrt(2+sqrt(2+sqrt(2+sqrt(2+sqrt4)))))=sqrt(2+sqrt(2+sqrt(2+sqrt(2+sqrt(2+2)))))=` 

`\ \ \ =sqrt(2+sqrt(2+sqrt(2+sqrt(2+sqrt4))))=sqrt(2+sqrt(2+sqrt(2+sqrt(2+2))))=` 

`\ \ \ =sqrt(2+sqrt(2+sqrt(2+sqrt4)))=sqrt(2+sqrt(2+sqrt(2+2)))=sqrt(2+sqrt(2+sqrt4))=` 

`\ \ \ =sqrt(2+sqrt(2+2))=sqrt(2+sqrt4)=sqrt(2+2)=sqrt4=2` 





`f)\ sqrt(3*sqrt(3*sqrt(3*sqrt(3*sqrt(3*sqrt(3*sqrt9))))))=sqrt(3*sqrt(3*sqrt(3*sqrt(3*sqrt(3*sqrt(3*3))))))=` 

`\ \ \ =sqrt(3*sqrt(3*sqrt(3*sqrt(3*sqrt(3*sqrt9)))))=sqrt(3*sqrt(3*sqrt(3*sqrt(3*sqrt(3*3)))))=` 

`\ \ \ =sqrt(3*sqrt(3*sqrt(3*sqrt(3*sqrt9))))=sqrt(3*sqrt(3*sqrt(3*sqrt(3*3))))=`      

`\ \ \ =sqrt(3*sqrt(3*sqrt(3*sqrt9)))=sqrt(3*sqrt(3*sqrt(3*3)))=sqrt(3*sqrt(3*sqrt9))=` 

`\ \ \ =sqrt(3*sqrt(3*3))=sqrt(3*sqrt9)=sqrt(3*3)=sqrt9=3`